Imaging arterial wall disease - Hennerici, Michael G.; Meairs, Stephen (Cerebrovascular diseases, 2000)
Ultrasonographic imaging of the carotid arteries allows assessment of both early and advanced atherosclerotic disease. This noninvasive technique has played a central role in many recent epidemiological studies and is being used increasingly for evaluating the efficacy of atherosclerosis prevention trials. New developments in ultrasound equipment, the use of echocontrast agents, novel applications of three- and four-dimensional sonography and in vivo characterization of plaque constituents with high-resolution MRI have broadened the scope of imaging of arterial walls, providing both enhanced information on disease progression as well as new insights into pathomechanisms of carotid plaque embolization. This article highlights pertinent issues of imaging of arterial wall disease and discusses important areas of current and future research in this field.
Published online: November 17, 2004
Gesehen am 20.07.2022